Identification on Balinese Maintenance Factors: A Case Study Conducted to Ten Balinese Families in Singaraja - Nyoman Ayu Sri Desi Ariani (Universitas Pendidikan Ganesha, 2012)
This qualitative study aimed at identifying the reasons or the factors (environmental and personal) influencing ten Balinese families to use a certain language as their first language and identifying the number of ten Balinese families who are still using Balinese as their first language. The subjects of the study were ten Balinese families in Singaraja town in Buleleng regency. They were selected randomly. The data collected using the techniques of observation and interview. The obtained data were interpreted and discussed descriptively. From the ten Balinese families, five of them used Balinese as their first language and as their daily conversational tool with the personal factors as the most influencing factor.